Psychological healing function of poetry appreciation based on educational psychology and aesthetic analysis - Zhang, Weijin (Frontiers in Psychology, 2022)
With the development of society, the rapidly developing social environment has played a significant role in the particular group of college students. College students will inevitably suffer setbacks and psychological obstacles in their studies and daily life. This work aims to ameliorate college students’ various mental illnesses caused by anxiety and confusion during the critical period of status transformation. Educational psychology theory, aesthetic theory, and poetry appreciation are applied to the mental health education of college students to obtain a satisfying psychological healing effect. First, this work summarizes the connotation and characteristics of college student’s mental health and defines educational psychology. Secondly, the long tradition of Chinese poetry teaching is introduced. Besides, the theoretical basis of poetry therapy and aesthetic psychology is expounded, and foreign poetry is discussed. In addition, poetry appreciation is used to promote personality shaping and psychological healing of college students based on the theory of educational psychology and poetry appreciation psychotherapy. In addition, mental health education for college students is studied from the perspectives of psychological health, mental health education, college students’ mental health education, and appreciation of ancient poetry. In addition, the principle and significance of college students’ mental health education are discussed from the perspective of poetry appreciation. Finally, an experimental study is conducted on college students and patients in a specific hospital department by issuing questionnaires to verify the practical application effect of this method in psychotherapy. The survey results indicate that the scores of college students who have completed a one-semester poetry appreciation course in different dimensions of mental disorders are lower than those of those who have not completed the course. At the same time, in the scores of 16 personality traits, the positive trait scores of the experimental group are higher than those of the control group. Comparing scores before and after class also reflects the positive effect of poetry appreciation intervention on college students’ personality shaping. It can be concluded that poetry appreciation has a strong effect on promoting college students’ mental health and personality shaping and improving college students’ psychological problems.